Ecobricks Sebagai Edukasi Pengolahan dan Pemanfaatan Sampah Plastik untuk Siswa/i Sekolah Dasar - Farahdiansari, Ardana Putri; Maulana, Yoga; Febriansa, Nungki Dio; Utomo, Izza Ahmad; Al Khoirina, Anita Sari (Abdimas Universal, 2025)
Plastic waste is a significant global environmental issue with negative impacts on soil, water, air, and human health. Difficult to decompose, plastic accounts for about 15% of total domestic waste, and this issue is particularly acute in Bancer Village, Ngraho District, Bojonegoro Regency, which faces environmental pollution from plastic waste associated with schoolchildren's snacks. This community services aims to address the issue of plastic waste management in the village through an educational and practical ecobrick-making program involving students of SDN 1 Bancer. The program was conducted in two stages: first, a socialization effort on the classification of organic and inorganic waste to enhance students' awareness of the impact of plastic waste and the importance of waste segregation; second, a training session on creating ecobricks from plastic waste to demonstrate practical recycling applications. Results showed a significant improvement in students' understanding of waste classification, with 90% of students able to classify waste correctly after the socialization. The ecobrick-making training also provided practical skills for converting plastic waste into useful materials. This program positively contributes to waste management in Desa Bancer and has the potential to serve as a model for other communities. The awareness and skills developed are expected to bring significant improvements to environmental quality and promote sustainable waste management practices in the future.